Biocomposite-based fibrous scaffolds of natural rubber/polyhydroxybutyrate blend reinforced with 45S5 bioglass aiming at biomedical applications - Silva, Michael J. [UNESP]; Dias, Yasmin J.; Zaszczyńska, Angelika; Robles, Jaqueline Rojas; Abiade, Jeremiah; Kowalczyk, Tomasz; Kołbuk, Dorota; Sajkiewicz, Paweł Ł.; Yarin, Alexander L. (Wiley, 2024)
The solution blow spinning technique was used to fabricate a new biocomposite fibrous mat consisting of natural rubber (NR) and polyhydroxybutyrate (PHB) bioblend, with various loads of 45S5 bioglass (BG) particles. According to SEM analysis, NR fibers exhibited ribbon-like morphologies, whereas the addition of PHB resulted in improved fiber formation and a reduction in their diameter. In NR-PHB/BG biocomposites with varying BG loadings, typical thermal degradation events of PHB (stage i) and NR (stage ii) were observed. In comparison with pure PHB, the TG/DTG curves of NR-PHB/BG specimens revealed a lower stage i degradation peak. Such an outcome is possibly due to the fact that PHB in the NR-PHB fibers is located predominantly at the surface, that is, PHB is more susceptible to thermal degradation. The NR-PHB/BG biocomposite possessed an increased stiffness due to the addition of PHB and BG, resulting in an increased stress and a decreased strain at rupture compared to the pure NR and NR-PHB mats. DMA analysis revealed two well-defined regions, above and below the glass transition temperature (Tg), for the storage modulus (E') of the NR-PHB/BG specimens. The values of E' were in both regions for NR-PHB/BG specimens increased at higher BG content. The measured tanδ = E″/E' was used to determine the Tg value for all specimens, with Tg found to be in the −49 to −46°C range. Finally, NR-PHB/BG biocomposite fibrous were proven noncytotoxic by in-vitro testing on fibroblasts. These biocomposites enhanced cell growth, holding great promise for tissue engineering applications. Highlights: Solution blow spinning technique was used to produce three-phase biocomposite specimens. NR-PHB/BG fibrous mat specimens with a diameter of 9–10 μm were obtained. Although high BG loads are applied to the NR-PHB/BG specimens, they remain elastic and flexible. Fibrous biocomposite mats enhance cell growth and possess great potential for tissue engineering.
Keywords: 45S5 bioglass; biocomposite fibrous mat; biomedical applications; natural rubber; polyhydroxybutyrate; solution blow spinning